1970
DOI: 10.1084/jem.131.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Renal Toxicity of Heme Proteins and Their Derivatives: A Role in the Genesis of Acute Tubule Necrosis

Abstract: This investigation studies the toxicity of heme proteins and/or their break-down products on renal function. Heme proteinemia precedes acute tubule necrosis at a frequency great enough to suggest a causal relationship between the two events. Physiological and metabolic functions of kidney slices are investigated in several models of acute tubule necrosis. Organic acid and organic base transport is depressed earliest. These alterations in tubule function cannot be explained by ischemia or obstruction alone. Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…It is apparent, however, that when the filtered load of hemoglobin is increased, this homeostatic mechanism is easily overwhelmed and thus rendered relatively ineffective. The role of the adaptive heme oxygenase system 2048 Pimstone, Engel, Tenhunen, Seitz, Marver, and Schmid of the kidney in the multifactorial pathogenesis of hemoglobinuric nephropathy (33)(34)(35) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent, however, that when the filtered load of hemoglobin is increased, this homeostatic mechanism is easily overwhelmed and thus rendered relatively ineffective. The role of the adaptive heme oxygenase system 2048 Pimstone, Engel, Tenhunen, Seitz, Marver, and Schmid of the kidney in the multifactorial pathogenesis of hemoglobinuric nephropathy (33)(34)(35) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showed that infusion of hemoglobin after a multifactorial insult predisposed rats to kidney injury, including ischemic damage. 15 In addition, the presence of methemoglobin was associated with severe azotemia and tubular necrosis. 14 Infusion of hemoglobin in rats when the blood is acidemic also caused azotemia, but not as severe as that seen with methemoglobin.…”
Section: Hemolysis Caused By Thrombectomymentioning
confidence: 99%
“…However, this model reflects at least important aspects of the pathophysiological changes seen in human septic shock. The use of hemoglobin solutions prepared by lysis of red blood cells as substitute for blood transfusion was associated with serious side effects including kidney failure, intravascular coagulation, and anaphylactic reactions (28,29). Purification to remove erythrocyte stroma or contaminating lipopolysaccharide reduces but does not prevent toxicity because hemoglobin causes renal failure by intratubular precipitation of methemoglobin and free heme (33).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its affinity to NO, hemoglobin (Hb) could function as a scavenger to remove exessive amounts of NO and therefore could be of therapeutic use in septic shock (27). However, Hb itself can induce acute renal failure when infused intravenously (28,29). Polymers of Hb were originally developed as substitutes for blood transfusion and to improve tissue perfusion and oxygen delivery in hemorrhagic shock (30).…”
Section: Introductionmentioning
confidence: 99%